MORAL QUALITIES INHERENT IN A PERFECT PERSON, WHICH WERE PUT FORWARD IN THE PHILOSOPHICAL WORKS OF HUSSEIN VOIZ KOSHIF - Tolliboyev, Dilshod; Pirimov, Ganisher (Science technology&Digital finance, 2023)
This article discusses the mystical contradictions and spiritual and moral qualities of the perfect man and their significance today, put forward in the work "Futuvvatnomai Sultani" by Hussein Voiz Kashifi, a representative and theorist of the art of oratory, thinker, theologian.